Physical load, stress and musculoskeletal morbidity in administrative workers in the public sector - Castillo-Ante, Lesly; Ordoñez-Hernández, Cecilia; Calvo-Soto, Andrea Patricia (Universidad y Salud, 2019)
Introduction: Musculoskeletal disorders are associated with physical and organizational aspects of work, among others. Objective: To determine the relationship between physical load, levels of stress, and musculoskeletal morbidity in administrative workers in the public sector of Popayán (Colombia), between 2016 and 2017. Materials and methods: An analytical-correlational, cross-sectional, quantitative study of a random sample of 104 workers. The data collection instruments were: the Rapid Upper Limb Assessment (RULA), the Maslach Burnout Inventory (MBI) and the Standardized Nordic Questionnaire (Kuorinka et al., 1987). Uni- and bivariate analysis were conducted, as well as a Chi-square to test the hypothesis. Results: It was found that 76% of the workplaces require further research and need changes. 79% of employees experienced low fatigue levels, whereas 83% manifested depersonalization. During the last six months, the most common pains reported were neck pain (51%), followed by back pain (36%) and shoulder pain (33%). There was a statistically significant correlation between postural load and muscle pain (p=0.301). Conclusion: Although an increased postural load is related to neck pain, this pain is not associated with workplace stress.